School Dropouts: A careful look at the mental health of adolescents (Research, Society and Development, 2025)
The Brazilian psychiatric reform has transformed mental health care, promoting social inclusion and the autonomy of individuals suffering from mental illness. In the context of children and adolescents, the Child and Adolescent Psychosocial Care Centers (CAPSi) were created to offer psychosocial rehabilitation and clinical follow-up. This study investigates the factors associated with school dropout among adolescents in psychological distress treated at this service. This is a qualitative study based on semi-structured interviews with six adolescents who had dropped out of school and were actively participating in therapeutic groups. The data reveals that psychological distress, bullying, discrimination and learning difficulties are central factors in school dropout. Negative comments from teachers and traumatic experiences at school aggravated the dropout. Dropping out of school is directly related to failures by the educational system to meet students' emotional and cognitive demands. There is an interdependence between mental health and staying in school. It is essential to promote welcoming school environments, with trained professionals and mental health support, in order to reduce dropout and support students' integral development.